STUDY OF THEORY, METHOD, APPLICATION OF GOTHIC CHURCH ARCHITECTURE - Adimas Kristiadi (ARSITEKTURA, 2018)
The architecture of Gothic church is the outcome from creation process of knowledge by human in 12th – 15th Century which originating from France, which one the evolution from Romanesque church architecture (10th – 13th Century). The word of “evolution” is being a keyword and be a reason of Gothic church, to change characters from Romanesque church architecture are monastic buildings (not large), heavy in appearance, simple in construction to be a larger and finer, much details and symbols, construction and ornament is advancing and improving, there is an effort to enter natural lighting. There is competition in 12th – 15th Century about bigger and magnificent building of church in Europe. The method is literature studies with analytical descriptions. The results are: 1) The basic theory of evolution is dignity, Gothic church architecture is built with the intention of giving honor of the highest to God. The concepts are verticalism, transparent, religious symbolism. The methods is following the concepts that are heighten (heightening structure), mitigate (lightening structure), brighten (natural lighting), symbolize (enrich symbols). The application is realized with: floor plan as cross, pointed arch, ribbed vault, flying buttress, pinnacles, flamboyant decoration, large windows filled with rich stained glass.